Developing Our Policy Know-How: Why Policy Should Be Part of Music Educator Identity. (September 2020) - Schmidt, Patrick
Policy is a critical practice that can be a valuable companion to music educators—alongside their pedagogical and content knowledge. This outlook challenges the position that teachers are subject to policy, reclaiming the necessity and value for teachers to see themselves as policy partners or policymakers in practice. The article explores three premises: (1) Today more than ever, policy matters; (2) there are important distinctions between policy and advocacy, and we should understand them and be engaged in both; and (3) expanding music teachers' policy know-how can positively impact the role they play in school communities. The article offers pathways for policy thinking and action—policy know-how—as a significant element in the education and the professional life of music educators.